Effectiveness of male engagement in maternal health - Nyanzira, Norah C. (Midlands State University, 2018)
The study examined the effectiveness of male engagement in maternal health in ward 28 of Chipinge. The area has experienced high maternal mortality rate as well as poor maternal health services. 64 respondents from the eight villages were identified four representatives from each village. The researcher used focus group discussions and structured questionnaires as the data collection tools. The findings are grounded on the structured questionnaires directed to the adult women and men, adolescent women and men and interviews to both adult and adolescent women as well as men. The study found that there is poor male engagement in maternal health and this has had negative repercussions on the state of maternal health in the area. Patriarchy has been the major cause for lack of male engagement in maternal health and it has allowed men to make uniformed decisions in terms of maternal health which has had dire effects on maternal health. However, the respondents noted that exclusion of the males in maternal health issues is due to other health facility related reasons like the behavior of the health staff. Also the campaigns that are done in the area mostly exclude men as they present maternal issues as purely feminine.